P2O5/SiO2 : A Simple and Effective Catalyst for the Synthesis of N-substituted 1-Alkyl and 1-Aryl 3-Aminoisoquinolines - Mendez, Leticia Jesica (2013)
A synthesis of N-substituted 1-alkyl and 1-aryl 3-aminoisoquinolines by cyclocondensation of 2- acylphenylacetonitriles with aliphatic and aromatic amines using P2O5/SiO2 as catalysts is described. Selectivity, simplicity of operation and easy work-up are some advantages of this method.